Radiography used to measure internal spinal cord deformation in an in vivo rat model. (11th April 2018) - Lucas, E.; Whyte, T.; Liu, J.; Tetzlaff, W.; Cripton, P.A.
Abstract: Little is known about the internal mechanics of the in vivo spinal cord during injury. The objective of this study was to develop a method of tracking internal and surface deformation of in vivo rat spinal cord during compression using radiography. Since neural tissue is radio-translucent, radio-opaque markers were injected into the spinal cord. Two tantalum beads (260 µm) were injected into the cord (dorsal and ventral) at C5 of nine anesthetized rats. Four beads were glued to the lateral surface of the cord, caudal and cranial to the injection site. A compression plate was displaced 0.5 mm, 2 mm, and 3 mm into the spinal cord and lateral X-ray images were taken before, during, and after each compression for measuring bead displacements. Potential bead migration was monitored for by comparing displacements of the internal and glued surface beads. Dorsal beads moved significantly more than ventral beads with a range in averages of 0.57–0.71 mm and 0.31–0.35 mm respectively. Bead displacements during 0.5 mm compressions were significantly lower than 2 mm and 3 mm compressions. There was no statistically significant migration of the internal beads. The results indicate the merit of this technique for measuring in vivo spinal cord deformation. The pattern of bead displacements illustrates the complex internal and surface deformations of the spinal cord during transverse compression. This information is needed for validating physical and finite element spinal cord surrogates and to define relationships between loading parameters, internal cord deformation, and biological and functional outcomes.